2011
DOI: 10.1086/662620
|View full text |Cite
|
Sign up to set email alerts
|

A Multifaceted Intervention Strategy for Eradication of a Hospital-Wide Outbreak Caused by Carbapenem-Resistant Klebsiella pneumoniae in Southern Israel

Abstract: This intervention produced an enormous impact on patient location, surveillance cultures, and antibiotic policies and a massive investment in infection control resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 13 publications
0
66
0
1
Order By: Relevance
“…Dedicated nursing staff is probably one of the most relevant measure to avoid cross transmission [15,[17][18][19]. In the context of an epidemic, cohorting patients with dedicated nursing staff in three different groups (cases, contacts and newly admitted patients) was shown to be effective in controlling the outbreak [6,11,17]. The present study shows that dedicating staff to an index case carrying CPE also prevents the occurrence of outbreaks.…”
Section: Number Of Events Proportion Of Outbreaks Among Eventsmentioning
confidence: 49%
See 2 more Smart Citations
“…Dedicated nursing staff is probably one of the most relevant measure to avoid cross transmission [15,[17][18][19]. In the context of an epidemic, cohorting patients with dedicated nursing staff in three different groups (cases, contacts and newly admitted patients) was shown to be effective in controlling the outbreak [6,11,17]. The present study shows that dedicating staff to an index case carrying CPE also prevents the occurrence of outbreaks.…”
Section: Number Of Events Proportion Of Outbreaks Among Eventsmentioning
confidence: 49%
“…A specific early warning system organised by the French Health authorities at the national level to systematically collect information on CPE cases, reported 113 cases in 2011 for the whole country [13]. Bundle measures similar to those described in the present study have been associated with the limitation of CPE spread in Israel where CPE are endemic [15][16][17].…”
Section: Number Of Events Proportion Of Outbreaks Among Eventsmentioning
confidence: 63%
See 1 more Smart Citation
“…One study found that healthy patients who tested positive for carbapenem-resistant A. baumannii cultures had 8.4 times the risk of developing a subsequent infection than patients who remained negative on surveillance cultures (15 ). In another study, 32 of 433 patients (7.4%) with carbapenem-resistant K. pneumoniae developed an infection within 2-40 days from colonization to infection (16 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has, in fact, been proposed that, given the ease of transfer and acquisition of these genes, outbreaks must be controlled early on in order to avoid hospital dissemination (3,6,12). Indeed, surveys in regions of endemicity, such as Israel, Italy, and the northeastern United States, have reported successful control management of infections caused by KPC producers (1,2,4,8,17,26). In the present prospective study, we documented the effectiveness of containment strategies in combating the secondary transmission of imported KPC clones from other Greek tertiarycare facilities.…”
Section: Discussionmentioning
confidence: 99%